EDUKASI GERSIK PADA PEDAGANG PASAR TRADISIONAL PEMATANG GUBERNUR, KOTA BENGKULU DALAM MENGHADAPI PANDEMI CODID-19 - Anandyawati, Anandyawati; Pasaribu, Esti; Setiono, Panut; Yuristia, Rahmi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Gersik Education is an activity to socialize the movement to clean yourself and the surrounding environment to prevent the spread of the Covid-19 virus. This service activity was carried out at the Traditional Afternoon Market, Pematang Governor Village, Bengkulu City. The activity was carried out from May to August 2020. This activity involved 149 traders. This service activity consists of three main activities, namely: first, socialization about GERSIK (the movement to clean oneself and the environment) through speeches and using posters, second, the distribution of masks and hand sanitizers and the third to build public facilities in the form of hand washing stations. Based on the results of the implementation, periodic monitoring and evaluation of community service activities, it can be concluded that the community service activities specifically Covid-19 at the Governor's Evening Market, Bengkulu City are running effectively. This can be seen from the high enthusiasm of the community in participating in outreach activities carried out by the service team and the increasing level of awareness of traders to use masks and wash their hands.